Examining infertility-related stress and quality of life in women who undergo and forgo infertility treatment - Thomas, Emily (East Carolina University, 2023)
Infertility treatments are known to cause high levels of stress and low quality of life (QoL) in women who experience infertility, or the inability to conceive after a year of unprotected sexual intercourse. Women may discontinue infertility treatments for a variety of reasons; however, relationships between infertility-related stress and QoL have not been examined among women who discontinue or do not initiate treatments. The purpose of this study was to examine infertility-related stress and QoL among women in infertility treatments and women who discontinue, or do not follow through with infertility treatments. Using the parent study, infertility-related stress was measured with the COMPI-FPSS tool (martial, social, and personal stress), and the Fertility Quality of Life (FertiQoL) scale to measure 4 core QoL subscales (emotional, mind/body, relational, and social). Results were examined and compared among 70 women who were not receiving infertility treatments and 166 women receiving infertility treatments. Statistical analysis using SPSS software included descriptive statistics, crosstabs, independent t-tests, and a binary logistic regression analysis to examine variables that predicted treatment withdrawal. No statistically significant differences in infertility-related stress and QoL were found between the two groups. The logistic regression showed the Cox & Snell R2 =.115 and the Nagelkerke R2 =.163 for the full model. Three of the predictors were statistically significant, with odds ratios 2.50 for income, 2.49 for QoL dissatisfaction, and 2.40 for infertility duration 3 years or greater. Significant differences were found between the groups’ QoL satisfaction rating and health rating. Findings from this study indicate infertility-related stress and QoL are similar among women who forgo infertility treatments and women receiving infertility treatments, highlighting the need for health care providers to offer emotional support services to women who are diagnosed with infertility regardless of their treatment status. Future studies should explore psychological well-being of women who forgo or discontinue infertility treatments and further examine reasons for infertility treatment withdrawal.
Keywords: Infertility; stress; quality of life; discontinuation